Developing a Culturally Responsive E-Module: Integrating Baduy Traditional Wisdom into Digital Citizenship Education - Damanhuri, Damanhuri; Hasani, Aceng; Jamaludin, Ujang (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The integration of local wisdom into digital learning is essential to foster culturally relevant and engaging education. This development research aims to create and validate a citizenship education e-module that incorporates the indigenous knowledge of the Baduy community in Indonesia. Using a 4D (Define, Design, Develop, Disseminate) model, this research involves needs analysis, module design, and expert validation. The electronic module, designed with Canva and Heyzine Flipbook, integrates Baduy’s core values such as collaboration, environmental awareness, and customary law. Validation by media experts using Aiken’s V formula resulted in a score of 0.88, indicating a ‘highly valid’ product. The results demonstrate the feasibility of creating high-quality interactive digital learning resources that effectively instill local cultural values. This electronic module is poised to enhance civic education by making it more contextual, enhancing cultural literacy, and strengthening national identity, as well as being ready for empirical testing. This research is a pioneer in designing and validating Citizenship Education e-modules based on Baduy local wisdom, using development (4D) and empirical validation (Aiken’s V) approaches, so as to make conceptual, methodological, and practical contributions to the integration of local culture in digital education.